Lessons from a catalogue of 6674 brain recordings - Alexis DJ Makin; John Tyson-Carr; Giulia Rampone; Yiovanna Derpsch; Damien Wright; Marco Bertamini (eLife, 2022)
It is now possible for scientists to publicly catalogue all the data they have ever collected on one phenomenon. For a decade, we have been measuring a brain response to visual symmetry called the sustained posterior negativity (SPN). Here we report how we have made a total of 6674 individual SPNs from 2215 participants publicly available, along with data extraction and visualization tools (https://osf.io/2sncj/). We also report how re-analysis of the SPN catalogue has shed light on aspects of the scientific process, such as statistical power and publication bias, and revealed new scientific insights.